Understanding the Impact of Online Social Interactions on Social Behavior - Goreti Murni, Maria; Angger, Alek; Ario, Arbi (Journal Social Humanity Perspective, 2023)
The way people engage and communicate in the modern world has undergone a transformation thanks to social media platforms and online communities. This study explores the dramatic effects of online social interactions on interpersonal relationships, emotional health, and social conduct. This study offers a thorough explanation of the dynamics at work in digital social Behaviour by drawing on theoretical frameworks from psychology, sociology, and communication. The formation and expression of social identities, the pursuit of social rewards, and the dissemination of information through various digital media are all influenced by online interactions, as explored through the theoretical lenses of Social Identity Theory, Social Exchange Theory, and Media Richness Theory. The study examines the good and negative effects on people's emotional wellbeing of a variety of social Behaviours that appear in online contexts, such as the development of helpful virtual communities and the spread of harmful content. To further shed light on how virtual connections affect empathy, emotional contagion, and mental health consequences, the psychological and emotional components of online social interactions are carefully investigated. In order to better understand how people interact with virtual reality (VR) environments and form social relationships as avatars, the study also looks into the developing field of social Behaviour in VR environments. In conclusion, navigating the intricacies of the digital age requires an awareness of the effects of online social contacts on social Behaviour.